Understanding Hindi–English Code Switching in Indian Classrooms - Pallavi (JOURNAL OF INDIAN EDUCATION, 2016)
Despite the fact that code switching between Indian languages and English has emerged as a popular trend, especially among the Indian youth, it is castigated as an inappropriate form of language use by many. Popular perceptions interpret code switching as being language corruption, accepting its occurrence only in informal conversations rather than in formal. The concomitant diffusion of the trend of code switching and various perceptions associated with it has intercepted conversations that occur in Indian classrooms. Disregarding the popular notion that interprets switching between languages as lack of competence in the base language, this paper undertakes an analysis of the nature of code switching that occurs in the context of education by examining actual classroom conversations. The aim is to trace the multiplex of social and functional roles that code switching plays when it occurs within classroom transactions.